Digital multimedia books produced using iBooks Author for pre-operative surgical patient information. (October 2014) - Briggs, Matthew; Wilkinson, Caroline; Golash, Aprajay
Abstract Presenting patients with medical information and ensuring informed consent can be difficult due to patients with varying levels of literacy, physical and mental disabilities and spoken languages. Patients obtaining information from external sources, such as the internet, can also be problematic as the information can be irrelevant, inaccurate or misleading. A patient satisfaction study was performed in order to assess the effectiveness of using ebooks in order to communicate pre and post surgical information to neurosurgical patients. 3 digital books were produced using iBooks Author (a free desktop publishing program designed by Apple) including ACDF (anterior cervical discectomy and fusion), lumbar laminectomy and lumbar discectomy. Each book contained written information organised into sections and chapters along with an array of multimedia elements including 3D animations, interactive diagrams, 3D models of anatomy and patient experience videos. 32 volunteer patients were then presented with the digital books via an iPad during their preoperative assessment and then asked to complete a questionnaire. The results demonstrated a demand for this type of digital presentation of medical information and also showed patients no longer felt the need to seek further information from external sources.